Prevalence of Peripheral Arterial Disease (PAD) in End Stage Renal Disease (ESRD) Patients on Hemodialysis: A Study from Central Nepal - Ghimire, M; Pahari, B; Das, G; Das, GC (Kathmandu University Medical Journal, 2015)
Background Peripheral arterial disease is a common condition in the hemodialysis population with an estimated prevalence ranging from 17-48%. Many studies have been conducted to know the prevalence of peripheral vascular disease in hemodialysis population. However no such study has been conducted so far in Nepal.Objective This study was carried out with an objective to assess the prevalence of Peripheral Arterial Disease in End Stage Renal Disease Patients on Hemodialysis.Method Fifty patients with a diagnosis of End Stage Renal Disease (irrespective of the underlying cause), and those who were on hemodialytic support for more than 3 months were studied over a period of one year. Peripheral arterial disease was diagnosed on the basis of the ankle –brachial index, which was the ratio of the resting systolic blood pressure in the arteries of the ankle to that of the brachial artery, measured by using a standard mercury manometer with a cuff of appropriate size and the Doppler ultrasound. Patients with ankle –brachial index ?0.9 were considered positive for peripheral arterial disease.Result A total of 50 End Stage Renal Disease patients were analyzed. The mean age of the patient was 49.81±12.63 years. The age range was from 18- 79 years. Majority of them were males 64% (n=32). Peripheral arterial disease defined by ankle –brachial index ?0.9 was present in 30% (n=15) of patients. The three major cause of End Stage Renal Disease in the study population was Chronic Glomerulonephritis 40 % (n=20), Type 2 Diabetes Mellitus 28 % (n=14) and Hypertension 24 % (n=12). Type 2 Diabetes Mellitus was the commonest cause 53% (n=8) of End Stage Renal Disease in patients with peripheral arterial disease followed by hypertension 33% (n=5). On univariate analysis, peripheral arterial disease was found to be significantly associated with age >40 years (p value= 0.003; OR=14.8; CI=1.75-125.27), Type 2 Diabetes Mellitus (p value= 0.009; OR=5.4; CI=1.44-21.14), parasthesia of lower limbs (p value= 0.001; OR=10; CI-2.31-43.16), and intact PTH >300 ng/ml (p value =0.006; OR=5.7; CI=1.55-21.50). However on multivariate analysis only parasthesia of lower limbs and intact PTH >300 ng/ml were significantly and independently associated with peripheral arterial disease, while other variables were not significant.Conclusion Peripheral arterial disease was common occurrence in End Stage Renal Disease patients on hemodialysis. Ankle –brachial index needs to be included as a routine assessment in End Stage Renal Disease patients to detect peripheral arterial disease at its earliest.Kathmandu University Medical Journal Vol.12(3) 2014; 181-184